New e-learning platform for operations management via MOOC / Nooradzlina Mohd Pauzi and Mas Ayu Diana Mohd Fauzi - Mohd Pauz, Nooradzlina; Mohd Fauzi, Mas Ayu Diana (2018)
It cannot be denied that operations management concepts are much applicable in our daily life. However, students usually fail to relate the concept and elements of operations management in theirs. Hence, it is a challenge for educators in making students to understand and later appreciate this concept in their life’s. Educators nowadays must find some methods or techniques that can improve their teaching and learning. Usually, most of the educators are using conventional notes with simple slides presentations. This conventional teaching method had made the students feel unexcited and bored in the class. To grab the attention of students, electronic teaching method or known as Massive Open Online Course (MOOC) was introduced as part of the additional teaching aids. Various attractive features in learning activities were offered in MOOC. Learning activities like puzzle, quizzes, matches the right answer will help to develop active learning via MOOC. This method may help the students to explore and understand the exciting concept of operations management. It may also create more knowledge sharing between educators and students in the future not only in Malaysia but all over the globe